Ionisation differential cross section measurements for N2 at low incident energy in coplanar and non-coplanar geometries. (15th September 2016) - Sakaamini, Ahmad; Amami, Sadek; Murray, Andrew James; Ning, Chuangang; Madison, Don
Abstract: Ionisation triple differential cross sections have been determined experimentally and theoretically for the neutral molecule N2 over a range of geometries from coplanar to the perpendicular plane. Data were obtained at incident electron energies ∼10 and ∼20 eV above the ionisation potential of the 3 σ g, 1 π u and 2 σ g states, using both equal and non-equal outgoing electron energies. The data were taken with the incident electron beam in the scattering plane ( ψ  = 0°), at 45° to this plane and orthogonal to the plane ( ψ  = 90°). The set of nine measured differential cross sections at a given energy were then inter-normalised to each other. The data are compared to new calculations using various distorted wave methods, and differences between theory and experiment are discussed.